Where the private meets the public: Results of a survey of library professionals' observed student use of academic library spaces for prayer. Issue 2 (3rd April 2019) - Riehman-Murphy, Christina; Mross, Emily
Abstract: Reports of college students using the library for spiritual practices, including prayer and meditation, consist mainly of anecdotal observations, news stories, or press releases about the creation of such spaces within academic libraries. Driven by their own experiences with students using library spaces for prayer, the authors examined how prevalent this was across US academic institutions. Using a large-scale national survey, this study found library professionals observe a wide range of student prayer behavior in a variety of library spaces, regardless of institutional or campus demographics. The results provide academic libraries with evidence to support accommodating students' spiritual needs in library spaces.